Dissecting the causal pathway linking HbA1c to oral cavity cancer via immune cell modulation: a bidirectional mendelian randomization analysis - Wang, Jieqi; Zhang, Zhe; Wang, Yujia; Li, Bowen; Zheng, Meihua; Li, Jinsong (Frontiers in Oncology, 2026)
ObjectiveTo investigate the immune-mediated mechanisms underlying the causal link between HbA1c and oral cavity cancer.MethodsA bidirectional two-sample Mendelian randomization (MR) framework was employed, utilizing genome-wide association study (GWAS) data on HbA1c (n=46,368), oral cavity cancer (357 cases/372,016 controls), and 731 immune cell traits. The primary IVW analysis was supported by sensitivity analyses, including Cochran’s Q, I², MR-Egger, and leave-one-out, to ensure robustness. A multivariable MR (MVMR) was implemented to investigate the mediating effect of immune cells within the causal pathway linking HbA1c and oral cavity cancer. In vitro experiments evaluated the impact of advanced glycation end products (AGEs) on oral squamous cell carcinoma (OSCC) viability and CD8+ T cell function.ResultsGenetically elevated HbA1c was causally associated with the risk of oral cavity cancer (OR = 0.9993, 95% CI: 0.9988–0.9997, P = 0.0021). HbA1c significantly influences the activity of activated B cells and T cells (P < 0.05). MVMR analysis showcased considerable variation across immune cell types in relation to the HbA1c-oral cavity cancer relationship (P < 0.05). Importantly, reverse MR analyses revealed no significant bidirectional association between oral cavity cancer and HbA1c (OR = 0.1591; P = 0.1732). In vitro, AGEs did not alter OSCC cell viability but suppressed CD8+ T cell production of IFN-γ and GZMB, increased oxidative stress, and reduced tumor cell susceptibility to T-cell cytotoxicity (all P<0.05).ConclusionThis study provides genetic and experimental evidence for a protective, immune-mediated role of HbA1c in oral cavity cancer. While AGEs do not directly impact OSCC viability, they impair CD8+ T cell function via oxidative stress, highlighting the interplay between glycemic control, immune modulation, and carcinogenesis.